2016
DOI: 10.1039/c6ra90120d
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Self-assembly of silicon/carbon hybrids and natural graphite as anode materials for lithium-ion batteries

Abstract: Correction for ‘Self-assembly of silicon/carbon hybrids and natural graphite as anode materials for lithium-ion batteries’ by Aoning Wang et al., RSC Adv., 2016, 6, 104995–105002.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is reported that there are different degrees of defects on the amorphous substances, which can provide active sites for Li + to embed in, leading to increasing specific capacity. 20,21 Figure 1a shows TG curves of all samples, which were heated under air atmosphere. A mass loss appears at around 100°C for all the samples, which is ascribed to the evaporation of water.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that there are different degrees of defects on the amorphous substances, which can provide active sites for Li + to embed in, leading to increasing specific capacity. 20,21 Figure 1a shows TG curves of all samples, which were heated under air atmosphere. A mass loss appears at around 100°C for all the samples, which is ascribed to the evaporation of water.…”
Section: Resultsmentioning
confidence: 99%